Granular formulation of endophytic fungus, Hendersonia toruloidea GanoEF1 for controlling Ganoderma disease and promoting oil palm growth - Ramli, Nur Rashyeda (2018)
Oil palm is one of the important crops in Malaysia and plays an important role in the agricultural and economic development of the country. Basal stem rot (BSR) caused by Ganoderma boninense is the biggest threat for oil palm production and has been documented to cause a huge damage to the oil palm industry in Malaysia. There is yet an effective control measure for BSR disease. Endophytic fungi have been previously studied and identified as potential biological control agents of many crop diseases. Isolate Hendersonia toruloidea GanoEF1 is a novel and promising biological control agents against G. boninense. The use of endophytes in form of formulated product is preferred and sought as such preparations offer many advantages during application in the field. Therefore this study was designed with the specific objectives to (i) determine the compatible carriers for viability and quality of H. toruloidea GanoEF1 in the preparation of granular formulation, (ii) investigate the effects of granular formulations of H. toruloidea GanoEF1 for controlling BSR in oil palm, (iii) determine the biochemical compounds released in oil palm treated with H. toruloidea GanoEF1, and (iv) study the effects of the granular formulations developed of on oil palm growth. H. toruloidea GanoEF1 isolated from healthy oil palm roots was cultured on potato dextrose agar (PDA) media. A suspension containing 10⁸ CFU ml⁻¹ of the conidia cells was prepared as granular formulation by using empty fruit bunch (EFB), rice bran (RB), talc powder, paddy husk (PH) and sawdust (SD) as nutrient supplement mixed with inert ingredient of either kaolin or palm kernel cake powder in the solution containing alginate-pectin as a binder. The best ratio of alginate:pectin for optimum growth of H. toruloidea GanoEF1 was 1:3 at temperature 35 ºC with the highest number of conidia cell recorded was log 10⁸ CFU g⁻¹ at 30 days after storage. Three best nutrient carrier of EFB, RB and SD that succeeded to sustain the viability of H. toruloidea GanoEF1 were further formulated with kaolin (K) or palm kernel cake (PKC) and tested for their viability over 12 months storage and efficacy against G. boninense. Amongst them, three granular formulation of empty fruit bunch-kaolin (EFB-K), empty fruit bunch-palm kernel cake (EFB-PKC) and rice bran-palm kernel cake (RB-PKC) showed highest conidia viability of H. toruloidea GanoEF1 more than 10⁵ CFU g⁻¹ and recorded more than 50% of percentage inhibition of radial growth (PIRG) values. The effectiveness of H. toruloidea GanoEF1 in EFB-PKC, EFB-K and RB-PKC was then evaluated in the glasshouse on their efficacy against G. boninense. Disease suppression was highest in the treatment that had the application of H. toruloidea GanoEF1 in EFB-PKC with a disease reduction of 65.92% (P<0.05). The percentage of dead seedlings also was significantly lowest in seedlings treated with H. toruloidea GanoEF1 in EFB-PKC (26.7%) as compared to the control seedlings (93.3%). The lower percentage of dead seedlings indicates that the lower infection of BSR occurred. Furthermore, the production of POX and PPO were detected in the seedlings pre-inoculated with H. toruloidea GanoEF1 and significantly higher than control treatment at the post G. boninense challenge inoculation indicating induced resistance is one the mechanism of H. toruloidea GanoEF1 to control Ganoderma infection. The effect of the formulations on plant growth showed the seedlings treated with H. toruloidea GanoEF1 in EFB-PKC gave significantly (P<0.05) highest results on plant height (98.61 cm), girth (38.7 mm), number of frond (11.0), chlorophyll content (60.85 µg/L), root biomass (42.5 g) and leaves biomass (70.1 g) respectively, followed by seedlings treated with granular formulation of EFB-K, RB-PKC and control treatment. The oil palm roots colonized positively to H. toruloidea GanoEF1 inoculation with the highest population (between 2.0 x 10⁴ cfu g⁻¹ to 5.3 x 10⁷ cfu g⁻¹) was observed in the treatment of EFB-PKC and EFB-K granular formulations. This phenomenon was supported with the colonization of H. toruloidea GanoEF1 within the cortex of the root observed by using transmission electron microscopy (TEM). This study showed the H. toruloidea GanoEF1 in granular formulations containing carrier EFB-PKC was the most effective as biological control agent for controlling anoderma disease and promoting the growth of oil palm seedlings.